2015
DOI: 10.1111/infa.12116
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age, Psychological Maturity, Parenting Cognitions, and Mother–Infant Interaction

Abstract: In the context of the trend toward delayed childbearing, the aim of this study was to examine relations among maternal age and the quality of maternal interactive behavior at 7 months assessed using sensitivity and mind-mindedness, while also considering whether age effects were attributable to psychological maturity and parenting cognitions. Participants were 150 Australian mothers (mean age 33-years) and their firstborn infants who were participating in a prospective study of parenthood. Path analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 57 publications
(133 reference statements)
2
19
0
1
Order By: Relevance
“…Why do women who have deferred childbearing beyond their twenties seem to do well -not only during transition to parenthood -but also in the longer run in terms of disciplining less and raising children with fewer difficulties? As presented above, maturity tends to bring personal growth in terms of more stable emotional well-being, greater psychological hardiness and flexibility, higher level of personal integration,greater tolerance for complexity in emotional experience, and improved ability to forgive (Camberis et al, 2016;Carstensen et al, 2011;Cheng & Yim, 2008;Manners & Durkin, 2001;Mercer, 1986) ) If these aspects of maturity allow mothers to adopt a sound balance between freedom and control in their parenting style, the theory of the more authoritative parenting style may help explain maturity effects on long run child outcomes (Baumrind, 2013).The authoritative parenting style has been linked with children's, adolescent's and youth's positive development within the temperamental, conduct, peer and prosocial domains (Cavell, Harrist & Del Vecchio, 2013;Morris, Cui & Steinberg, 2013;Sorkhabi, 2013). The current study found correlations between the higher use sanctions and lower child adjustment within socioemotional domains at 7, 11, and 15 years (Table 3).…”
Section: Discussionmentioning
confidence: 94%
“…Why do women who have deferred childbearing beyond their twenties seem to do well -not only during transition to parenthood -but also in the longer run in terms of disciplining less and raising children with fewer difficulties? As presented above, maturity tends to bring personal growth in terms of more stable emotional well-being, greater psychological hardiness and flexibility, higher level of personal integration,greater tolerance for complexity in emotional experience, and improved ability to forgive (Camberis et al, 2016;Carstensen et al, 2011;Cheng & Yim, 2008;Manners & Durkin, 2001;Mercer, 1986) ) If these aspects of maturity allow mothers to adopt a sound balance between freedom and control in their parenting style, the theory of the more authoritative parenting style may help explain maturity effects on long run child outcomes (Baumrind, 2013).The authoritative parenting style has been linked with children's, adolescent's and youth's positive development within the temperamental, conduct, peer and prosocial domains (Cavell, Harrist & Del Vecchio, 2013;Morris, Cui & Steinberg, 2013;Sorkhabi, 2013). The current study found correlations between the higher use sanctions and lower child adjustment within socioemotional domains at 7, 11, and 15 years (Table 3).…”
Section: Discussionmentioning
confidence: 94%
“…(b) reported that adult mothers used more mind‐related comments than did teenage mothers during interaction with their infants. Older mothers may be more psychologically mature, and this maturity may in turn be associated with a greater capacity to take the child's perspective and more adaptive parenting cognitions (Camberis, McMahon, Gibson, & Boivin, ). Interestingly, this association had attenuated by 19 months, further supporting the need for more research on mind‐related discourse with toddlers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research results are in accord with Vondra and Belsky’s (1993) aforementioned statement. Camberis, McMahon, Gibson, and Boivin (2016) found that hardiness – an indicator of psychological maturity – was related to more sensitive mothering in infancy. Johnson, McMahon, and Gibson (2014) found the same indicator of psychological maturity (i.e., hardiness) to be related to more favourable bedtime cognitions in mothers.…”
Section: Parental Personality As a Determinant Of Parentingmentioning
confidence: 99%